Preliminary Studies on the Chemical Composition of Sound and Decayed Wood of Acacia mangium - Mansor, Halimathon (1989)
A comparison of the simple wood sugars and proximate chemical components in sound wood and wood with advanced decay of A. mangium was made. There were significant differences in the amounts of mannitol and alkali solubles between the sound and decayed wood. A slight difference was observed in the amount of alcohol-benzene and hot water solubles.